Competitiveness among employees: Descriptive study for the employees of Keynana Sugar Company - Ali Eltaher, Eltaher (Communications in Humanities and Social Sciences, 2023)
This study explores the levels of competitiveness among employees at the Keynana Sugar Company with an aim to establish correlations with key demographic variables, specifically the years of experience and gender. Utilizing descriptive methodology, the primary dataset was obtained through the application of the Hypercompetitive Attitude Scale. The research involved 49 participants (37 males and 12 females), and employed statistical analyses, such as T-tests and Pearson Correlation, to yield comprehensive insights. The findings of this research unveiled a marked prevalence of competitive attributes among employees at Keynana Sugar Company. Notably, the investigation revealed a lack of significant correlation between competitiveness and employees' years of experience. Furthermore, the analysis indicated no statistically significant variations in competitiveness based on gender among the employees at Keynana Sugar Company. This research significantly enriches the academic discourse on human resources competence, particularly within the domain of human resources psychology. By shedding light on the dynamics of competitiveness and its associations with demographic factors, the study provides valuable insights that can provide strategies for enhancing workforce effectiveness and organizational performance.